An assessment of the Indian Ocean mean state and seasonal cycle in a suite of interannual CORE-II simulations. (January 2020) - Rahaman, H.; Srinivasu, U.; Panickal, S.; Durgadoo, J.V.; Griffies, S.M.; Ravichandran, M.; Bozec, A.; Cherchi, A.; Voldoire, A.; Sidorenko, D .; Chassignet, E.P.; Danabasoglu, G.; et al.
Abstract: We present an analysis of annual and seasonal mean characteristics of the Indian Ocean circulation and water masses from 16 global ocean–sea-ice model simulations that follow the Coordinated Ocean-ice Reference Experiments (CORE) interannual protocol (CORE-II). All simulations show a similar large-scale tropical current system, but with differences in the Equatorial Undercurrent. Most CORE-II models simulate the structure of the Cross Equatorial Cell (CEC) in the Indian Ocean. We uncover a previously unidentified secondary pathway of northward cross-equatorial transport along 75 °E, thus complementing the pathway near the Somali Coast. This secondary pathway is most prominent in the models which represent topography realistically, thus suggesting a need for realistic bathymetry in climate models. When probing the water mass structure in the upper ocean, we find that the salinity profiles are closer to observations in geopotential (level) models than in isopycnal models. More generally, we find that biases are model dependent, thus suggesting a grouping into model lineage, formulation of the surface boundary, vertical coordinate and surface salinity restoring. Refinement in model horizontal resolution (one degree versus 1 4 degree) does not significantly improve simulations, though there are some marginal improvements in the salinity and barrier layer results. The results in turn suggest that a focus on improving physical parameterizations (e.g. boundary layer processes) may offer more near-term advances in Indian Ocean simulations than refined grid resolution. Highlights: Assessment of the Indian Ocean simulation from global forced sea- ice models. SST biases are ∼ 2 times smaller in forced simulations than the coupled simulations. Coupled model shows large inter-model spread over the eastern equatorial Indian Ocean. Refinement in model horizontal resolution does not significantly improve simulations. Uncover a secondary pathway of northward cross-equatorial transport along 75 °E. Models are unable to capture the observed thick barrier layer in the north Bay of Bengal.